2020
DOI: 10.1007/s13595-020-0931-y
|View full text |Cite
|
Sign up to set email alerts
|

Growth parameters and resistance to Sphaerulina musiva-induced canker are more important than wood density for increasing genetic gain from selection of Populus spp. hybrids for northern climates

Abstract: & Key message New genotypes of hybrid poplars from the Aigeiros and Tacamahaca sections have great potential for increasing genetic gain from selection. The most promising traits are associated with productivity and resistance to Sphaerulina musiva-induced canker while wood density can be selected for secondarily.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 44 publications
1
10
0
Order By: Relevance
“…This indicates that we must continue YBs to age 9 or 10 (full rotation) to obtain a reliable estimate of clone performance, as found by Stanton (2001). Similarly, Niemczyk and Thomas (2020) found that in northern climates of North America, 8 years is a reliable age at which to select fast-growing and disease-resistant poplar clones for commercial deployment. We already adopt this procedure in YBs to derive accurate biomass yield estimates for our clones.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…This indicates that we must continue YBs to age 9 or 10 (full rotation) to obtain a reliable estimate of clone performance, as found by Stanton (2001). Similarly, Niemczyk and Thomas (2020) found that in northern climates of North America, 8 years is a reliable age at which to select fast-growing and disease-resistant poplar clones for commercial deployment. We already adopt this procedure in YBs to derive accurate biomass yield estimates for our clones.…”
Section: Discussionmentioning
confidence: 81%
“…This fact is one of the strongest justifications for continuing poplar breeding programs. Recent papers on Sphaerulina musiva in hybrid poplars provide background on canker resistance research (Dunnell et al, 2016;Niemczyk and Thomas, 2020;Tabima et al, 2020), including the importance of deploying resistant clones.…”
Section: Discussionmentioning
confidence: 99%
“…Wood density is a strong determinant of mechanical strength, which affects wood quality and potential uses (Lundqvist et al 2018) and is considered the main physical variable and key index for evaluating wood quality and pulp yield (Ortega Rodriguez and Tomazello-Filho 2019). An increase in wood density has an important effect on the efficiency of pulp production (Niemczyk and Thomas 2020). Site is also an important factor with a strong effect on wood density (Dias et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Because large areas of single tree species have been grown over multiple years, the canker disease in these monoculture forests has become more and more serious over time. Poplar canker is also a major, global disease, causing varying degrees of forest death in the United States, Canada, Portugal and Afghanistan (Abelleira et al, 2019;Niemczyk & Thomas, 2020;Tabima et al, 2020). Botryosphaeria dothidea is one of the pathogenic fungi causing poplar canker.…”
Section: Introductionmentioning
confidence: 99%